2001
DOI: 10.1038/sj.ijir.3900656
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil improves nocturnal penile erections in organic impotence

Abstract: We studied the effects of sildena®l on nocturnal penile erections. We prospectively evaluated 36 patients with organic or psychogenic impotence and 5 normal, potent men. All patients completed 3 sessions of consecutive nights using the RigiScan Plus device. The ®rst two nights the patients were asked to take placebo before the session and to take 50 mg of sildena®l before the third session. In the organic impotence group the use of sildena®l induced a signi®cant improvement in time of rigidity 60 ± 100%, rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
0
22
1
Order By: Relevance
“…This could be attributed to the small sample size and to the wide Psychogenic erectile dysfunction MB Abdel-Naser et al variations between individual RigiScan recordings. 8,9,13 In contrast to these studies, however, the number of events was significantly improved, not only in the sildenafil citrate night, but also in night 4 in group I and in night 3 in group II. In group I, the improvement in night 4 when compared with that of night 3 (sildenafil citrate night) was insignificant.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…This could be attributed to the small sample size and to the wide Psychogenic erectile dysfunction MB Abdel-Naser et al variations between individual RigiScan recordings. 8,9,13 In contrast to these studies, however, the number of events was significantly improved, not only in the sildenafil citrate night, but also in night 4 in group I and in night 3 in group II. In group I, the improvement in night 4 when compared with that of night 3 (sildenafil citrate night) was insignificant.…”
Section: Discussioncontrasting
confidence: 47%
“…Several studies have shown improvement in almost all parameters of NPTR monitoring among patients with organic ED. 8,9 Regarding the impact of sildenafil citrate on NPTR in potent men, controversial results were obtained. Montorsi et al 9 showed that sildenafil citrate did not significantly improve nocturnal penile activity, whereas Yaman et al, 10 conducting a similar study with a larger sample, concluded that sildenafil citrate can improve nocturnal erectile quality not only in patients with ED, but also in potent men.…”
Section: Discussionmentioning
confidence: 99%
“…Terrades et al studied the effects of sildenafil on nocturnal penile erections of patients with organic or psychogenic impotence and normal potent men. 13 They found that sildenafil improved nocturnal penile erectile activity in patients with organic impotence. However, they also stated that this action could not be shown in patients with psychogenic impotence or in normal males.…”
Section: Discussionmentioning
confidence: 99%
“…Longer-lasting effects on endothelial function were reported after the nightly intake of sildenafil [5]. Moreover, taking sildenafil at bedtime improved nocturnal erections in healthy men and men with ED [3,[6][7][8]. Taking these results into account, we investigated the improvement and maintenance of erectile function (EF) and penile arteriogenic reactivity after daily PDE5 inhibitor treatment for 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…Contributing to the pathophysiology of vascular ED is an endothelial dysfunction as a result of the reduction of nitric oxide (NO) release from the endothelium [2]. In addition, increased fibrous tissue and decreased smooth muscle content might be the consequence of an insufficient oxygen supply to the organ in the absence of sexually stimulated or nocturnal erections [3]. The currently available selective PDE5 inhibitors reduces the turnover of cGMP, the NO second-messenger in the vascular muscles, and thereby increase the physiological activity of NO and improve endothelial function [4].…”
Section: Introductionmentioning
confidence: 99%